Identification of Factors Influencing the Development of Sports for Children with Special Needs - Ahmadi , Eskandar; Naderinasab, Mahdi; Hossieni, Seyed Sajjad; Nasiri Farsani , Mokhtar; Abdollahpour , Azam (Psychological Research in Individuals with Exceptional Needs, 2025)
The present study aimed to identify and analyze the key institutional, educational, socio-cultural, and psychological factors that influence the development of sports for children with special needs in Tehran. This study employed a qualitative research design using a phenomenological approach to explore the lived experiences and perceptions of stakeholders involved in inclusive sports. The participants included 21 individuals comprising teachers, parents, coaches, rehabilitation specialists, and policymakers selected through purposive sampling from Tehran. Semi-structured, in-depth interviews were conducted until theoretical saturation was achieved. Each interview lasted between 45 and 75 minutes and was transcribed verbatim. Data were analyzed using thematic analysis, following Braun and Clarke’s six-step model, with the assistance of NVivo 14 software to facilitate systematic coding and theme extraction. Trustworthiness of the results was ensured through member checking, peer debriefing, and maintaining an audit trail in accordance with Lincoln and Guba’s criteria. Analysis revealed four overarching themes: (1) Institutional and policy support, encompassing weak inter-organizational coordination and lack of inclusive policy frameworks; (2) Socio-cultural and family factors, including parental overprotectiveness, social stigma, and low public awareness; (3) Educational and infrastructural conditions, referring to limited accessibility, untrained staff, and insufficient adaptive facilities; and (4) Psychological and motivational dimensions, focusing on children’s self-efficacy, emotional development, and peer inclusion. These themes collectively highlight that inclusive sports development is constrained by structural, attitudinal, and environmental barriers, yet facilitated by supportive relationships and empathetic teaching practices. The findings demonstrate that effective development of sports for children with special needs requires integrated policy frameworks, inclusive educational reform, cultural transformation, and psychosocial empowerment.